Global burden and trends of testicular cancer in adolescents and young adults from 1990 to 2021, with predictions to 2035 - Shengjian Yu; Zeying Guo; Zijian Qiu; Liejiong Wang; Xiuxia Chen; Feng Xuan (Scientific Reports)
Abstract Testicular cancer predominantly affects adolescents and young adults (AYAs) aged 15–39 years. This study analyzed the global, regional, and national burden of testicular cancer among AYAs (1990 to 2021). Data from the Global Burden of Disease study was used to calculate age-standardized rates of incidence (ASIR), prevalence (ASPR), and disability-adjusted life years (ASDR). Trends were assessed using the Joinpoint regression and Bayesian age-period-cohort models, with projections up to 2035. Results showed the global ASIR of 4.05 (95% CI: 3.80–4.35), ASPR of 31.05 (95% CI: 28.88–33.68), and ASDR of 24.82 (95% CI: 22.99–26.91) per 100,000 in 2021, respectively. From 1990 to 2021, ASIR and ASPR increased, while ASDR remained relatively stable. Significant geographical disparities were observed, with Europe and Latin America showing higher burdens compared to Asia and Africa. The 25–29 age group had the highest age-specific rate of incidence (5.58; 95% UI: 5.25–5.97) and disability-adjusted life years (34.09; 95% UI: 31.55–37.11) per 100,000, while the 30–34 age group had the highest age-specific prevalence rate (43.12; 95% UI: 40.51–46.56) per 100,000 in 2021. By 2035, the global numbers of incidence and prevalence cases were projected to increase, with DALYs and age-standardized rates declining. These findings are crucial for informing global strategies in testicular cancer prevention.